AB0822 Adherence to Bisphosphonates Treatment of Osteoporosis. (10th June 2014) - Stoica, S.; Zugravu, G.
Abstract : Background: Osteoporosis is a serious public health concern and bisphosphonates (BPS) are the most common medications used in its treatment, whose main objective is to reduce the risk of fractures. Objectives: The aim of this study was to explore the experiences and perceptions of postmenopausal women regarding strategies to improve adherence to osteoporosis therapy. Methods: A total of 87 postmenopausal women between 45 and 70 years old with osteoporosis, currently taking BSP (30 with alendronate 70 mg/week, 28 with risedronate 35 mg/week and 29 with ibandronate 150 mg/month). All patients were interviewed and examined for the gathering of information on perceptions of their osteoporosis medications, their reasons for adherence and non-adherence to therapy, and the effectiveness of strategies they had tried to improve adherence at baseline, month 6 and month 12. Duration of therapy was measured by the count of days of therapy without of interruption of drug purchases greater than 2 weeks. Treatment compliance was evaluated with the Morisky Medication-taking Adherence Scale. Results: One year after initiating treatment for osteoporosis, 79.6% of patients with monthly bisphosphonates and 67.0% of patients with weekly bisphosphonates were not continuing to fill prescriptions. Six variables were associated with compliance: treatment administration frequency, perceptions of long-term treatment acceptability, perceptions of health consequences of osteoporosis, perceptions of knowledge about osteoporosis, exercise and mental quality of life. In multivariate analyses, the risk of adherence failure was higher for weekly BPS versus monthly BPS therapy (hazard ratio [HR]=2.7, p<0.01). Conclusions: Compliance to anti-osteoporosis treatments is poor. The monthly dosage is associated with greater adherence compared to weekly dosage. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5944